The Potential of Dehydrated Geniotrigona thoracica Stingless Bee Honey against Metabolic Syndrome in Rats Induced by a High-Carbohydrate, High-Fat Diet - Liyana Nabihah Ikhsan; Kok-Yong Chin; Fairus Ahmad (Pharmaceuticals)
Background/Objectives: Metabolic syndrome (MS) is diagnosed when at least three out of five key risk factors are present: obesity, high blood pressure, insulin resistance, high triglycerides (TG) and low high-density lipoprotein (HDL). MS is often associated with chronic low-grade inflammation. Recent studies have shown that raw stingless bee honey (SBH) can alleviate MS risk factors. However, the high moisture content in raw SBH predisposes it to fermentation, which can degrade its quality. Therefore, dehydrating SBH is necessary to prevent the fermentation process. This study aimed to compare the effects of dehydrated (DeGT) and raw (RGT) SBH from Geniotrigona thoracica species on high-carbohydrate, high-fat diet (HCHF)-induced MS in rats. Methods: Twenty-four male Wistar rats were divided into four groups: control (C), HCHF-induced MS without treatment (MS), HCHF-induced MS treated with DeGT (MS+DeGT) and HCHF-induced MS treated with RGT (MS+RGT). Group C received standard rat chow, while the other groups were fed with HCHF diet for 16 weeks. In the final eight weeks, two HCHF-induced groups received their respective SBH treatments. Results: Both DeGT and RGT treatments reduced energy intake, fat mass, high blood pressure, inflammatory (tumour necrosis factor-alpha (TNF-α)) and obesity (the leptin/adiponectin (L/A) ratio, corticosterone, 11 beta-hydroxysteroid dehydrogenase type-1 (11βHSD1)) markers, as well as prevented histomorphometry changes (prevented adipocyte hypertrophy, increased the Bowman’s space area and glomerular atrophy). Additionally, DeGT increased serum HDL levels, while RGT reduced serum TG, leptin and other inflammatory markers (interleukin-6 (IL-6) and interleukin-1 beta (IL-1β)), as well as hepatosteatosis. Conclusions: While DeGT demonstrates potential as a preventive agent for MS, RGT exhibited more pronounced anti-MS effects in this study.